2010
DOI: 10.1038/nature09270
|View full text |Cite
|
Sign up to set email alerts
|

Biological, clinical and population relevance of 95 loci for blood lipids

Abstract: Serum concentrations of total cholesterol, low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), and triglycerides (TG) are among the most important risk factors for coronary artery disease (CAD) and are targets for therapeutic intervention. We screened the genome for common variants associated with serum lipids in >100,000 individuals of European ancestry. Here we report 95 significantly associated loci (P < 5 × 10-8), with 59 showing genome-wide significant association wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

185
3,629
26
30

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 3,271 publications
(3,894 citation statements)
references
References 20 publications
185
3,629
26
30
Order By: Relevance
“…PCSK9 is the most established one, since it has been known for more than a decade that gain‐of‐function and loss‐of‐function variants in the PCSK9 gene increase (Abifadel et al , 2003) and decrease (Cohen et al , 2006) the risk of CAD and MI, respectively. GWAS also identified an association between common variants in the PCSK9 gene and both cholesterol levels (Teslovich et al , 2010) and CAD (Myocardial Infarction Genetics Consortium et al , 2009). PCSK9 functions in LDL cholesterol metabolism by tagging for the degradation of intracellular as well as extracellular LDL cholesterol receptors (Brautbar & Ballantyne, 2011).…”
Section: Novel Therapeutics In Lipid Metabolismmentioning
confidence: 99%
“…PCSK9 is the most established one, since it has been known for more than a decade that gain‐of‐function and loss‐of‐function variants in the PCSK9 gene increase (Abifadel et al , 2003) and decrease (Cohen et al , 2006) the risk of CAD and MI, respectively. GWAS also identified an association between common variants in the PCSK9 gene and both cholesterol levels (Teslovich et al , 2010) and CAD (Myocardial Infarction Genetics Consortium et al , 2009). PCSK9 functions in LDL cholesterol metabolism by tagging for the degradation of intracellular as well as extracellular LDL cholesterol receptors (Brautbar & Ballantyne, 2011).…”
Section: Novel Therapeutics In Lipid Metabolismmentioning
confidence: 99%
“…Epidemiologic studies have shown that elevated triglycerides correlate with elevated cardiovascular risk,4, 5 and the American Heart Association has long recognized that elevated triglycerides are an important marker of cardiovascular risk 6. More recently, genetic,7, 8, 9, 10, 11, 12, 13 genome‐wide analysis,14, 15, 16, 17 and mendelian randomization18, 19, 20, 21, 22 studies have suggested a causal role for triglycerides as a modifiable risk factor in the development and progression of ASCVD. Analyses from clinical data have demonstrated that lower on‐treatment triglycerides correlate with reduced cardiovascular risk 23, 24…”
mentioning
confidence: 99%
“…found that the polymorphism rs11613352 may contribute to attenuate cardiovascular risk by modifying plasma lipid levels in FH patients, as the TT genotype displayed a profile of lower TG and higher HDL‐C (Aledo et al., 2015). The association for lipids was similar to the GWAS study (Teslovich et al., 2010). Although a lipid association was not seen in the present male population, we confirmed it for increased HDL‐C seen with the TT genotype in 50‐year‐old women in the TAMRISK population ( p  = 0.001 for comparison of genotypes, n  = 300) (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Men with ANGPTL3 rs2131925 (T>G) T allele had more hypertension than those with the minor genotype GG. Previously, the TT genotype has been shown to be associated with increased TG and LDL‐C (Teslovich et al., 2010). We found no statistically significant association with lipids in our male population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation